Popularity, mood, energy, and typicality in music: A computerized analysis of 204,506 pieces - North, Adrian; Krause, A.; Sheridan, L.; Ritchie, D. (2018)
Several previous studies support the claim that liking for music can be predicted by its arousal-evoking qualities and typicality; and that emotional responses to music can be captured by two dimensions, namely sleepy-arousing and unpleasant-pleasant. The present research tests these ideas via all 204,506 pieces of music to have featured on sales and/or radio airplay charts in the United States, representing the entire commercial musical culture. Energy scores were related to popularity, although not always in the predicted direction. Atypical songs enjoyed more commercial success. Energy and beats per minute data were associated with seven mood scores for each piece, such that higher values were associated with the expression of moods toward the arousing pole of the sleepy-arousal dimension. Popularity was also associated with mood scores, demonstrating those moods associated most clearly with commercial success; and mood scores differed between genres, with implications for music therapy, research on music and mental health, and the uses of music in commerce.